EVALUATING RESPONSIBILITY ACCOUNTING EFFECTIVENESS UNDER RESOURCE CONSUMPTION ACCOUNTING METHOD-A CASE STUDY IN THE STATE COMPANY FOR THE PHARMACEUTICAL INDUSTRY AND MEDICAL APPLIANCES / SAMARRA - Yaseen Abbas Dawood; Asst. Prof. Dr. Laith Noman Hassoon (American Journals, 2023)
The search aimed to identify the possibility of using the method of resource consumption accounting as one of the modern methods in allocating costs and measuring variances and the impact of these variances on the effectiveness of responsibility accounting in industrial companies through its production of appropriate information, The search dealt with the theoretical framework for resource consumption accounting method, the theoretical framework for the responsibility accounting system, In order to achieve the objective of the search and test its hypothesis, the General Company for the manufacture of medicines and medical supplies in Samarra was chosen as the subject of the study, The application of the resource consumption accounting method was tested on the company's data according to a case study in order to identify the contribution of the information resulting from this method to the effectiveness of responsibility accounting for the company under study, The search concluded that the resource consumption accounting method is one of the important methods for managing costs as a result of its ability to provide information to measure and identify.
Keywords: Variances, Resource Consumption Accounting method, Responsibility Accounting